The concept of absent popular culture and its application to the Chilean case from a historical perspective - Sáez, Chiara (Universidad de Chile. Instituto de la Comunicación e Imagen, 2019)
Re-elaborating the categories of representation of the popular in Sunkel (1985), the concept of absent popular culture is proposed, whose foundation arises from the articulation of 3 theoretical matrices: Latin American comunicology of social change, cultural studies and decolonial thinking. The hypothesis is that the illustrated rational matrix was introduced into urban Latin American popular culture during the nineteenth century and its gradual institutionalization as a worker culture generated a process of internal divergence of the popular in the process of modernization, where popular culture -that were not massive or worker- was politically invisible. The well-founded identification of 12 expressions of popular culture absent in Chile from the beginning of the nineteenth century onwards allows us to conclude that there is a third way of existence of urban popular culture in the Latin American context, with an internal consistency despite historical transformations, whose discourses and representations should be analyzed thoroughly.